2008
DOI: 10.1085/jgp.200709896
|View full text |Cite
|
Sign up to set email alerts
|

Modular Design of Cys-loop Ligand-gated Ion Channels: Functional 5-HT3 and GABA ρ1 Receptors Lacking the Large Cytoplasmic M3M4 Loop

Abstract: Cys-loop receptor neurotransmitter-gated ion channels are pentameric assemblies of subunits that contain three domains: extracellular, transmembrane, and intracellular. The extracellular domain forms the agonist binding site. The transmembrane domain forms the ion channel. The cytoplasmic domain is involved in trafficking, localization, and modulation by cytoplasmic second messenger systems but its role in channel assembly and function is poorly understood and little is known about its structure. The intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
169
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(194 citation statements)
references
References 54 publications
23
169
1
1
Order By: Relevance
“…We found that neither the cation selectivity of the 5-HT 3A R (see also ref. 18) nor the anion selectivity of the α1 GlyR is any lower upon removal of their intracellular domains (P K + /P Cl -= 88 and P Cl -/P K + = 271, respectively; Fig. 2 E and F).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…We found that neither the cation selectivity of the 5-HT 3A R (see also ref. 18) nor the anion selectivity of the α1 GlyR is any lower upon removal of their intracellular domains (P K + /P Cl -= 88 and P Cl -/P K + = 271, respectively; Fig. 2 E and F).…”
Section: Resultsmentioning
confidence: 93%
“…S1; ref. 21) that ions must traverse upon entering or exiting the channel, and their removal was found to increase the 5-HT 3A R's single-channel conductance from <1 to 20-40 pS (9,18). Whereas the 5-HT 3A R has seven basic residues per subunit framing these portals, the muscle AChR has only two (e subunit) or three (α1, β1, and δ subunits), and although these residues exert little to no effect on the charge selectivity of wild-type pLGICs ( Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Of these subtypes, the 5-HT 3 receptor is a member of the superfamily of ligand-gated ion channel receptors. This family shares structural similarities with the nicotinic acetylcholine, glycine, and g-aminobutyric acid type A (GABA A ) receptors [3,11,12]. The 5-HT 3 receptors are widely distributed in both the central and peripheral nervous system and are involved in the physiologic and pathologic processes that mediate nausea, vomiting, peripheral nociception, and central antinociception [5,20].…”
Section: Introductionmentioning
confidence: 99%